2016
DOI: 10.1017/s0022149x16000183
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Orthocoelium streptocoelium (Digenea: Paramphistomidae) for comparison with other digeneans

Abstract: Orthocoelium streptocoelium is a common paramphistome species parasitizing the rumen and/or reticulum of small ruminants, leading to significant losses. This study first determined the complete mitochondrial (mt) genome of O. streptocoelium. The complete mt genome of O. streptocoelium was amplified, sequenced, assembled, analysed and then compared with those of other digeneans. The entire mt genome of O. streptocoelium is 13,800 bp in length, which is smaller than those of other digeneans except for Opisthorch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…It indicated that Paramphistomidae and Gastrothylacidae were more closely related than Diplodiscidae. In the group of Paramphistomidae and Gastrothylacidae, the five species of Paramphistomidae did not cluster together, O. streptocoelium formed a separate branch, which is consistent with previous study ( Zhao et al, 2017 ). Interestingly, the further analysis found that the flukes parasitic in amphibians (frogs) formed one group, and the flukes from ruminants (cattle, sheep, ect) clustered together and formed another group.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It indicated that Paramphistomidae and Gastrothylacidae were more closely related than Diplodiscidae. In the group of Paramphistomidae and Gastrothylacidae, the five species of Paramphistomidae did not cluster together, O. streptocoelium formed a separate branch, which is consistent with previous study ( Zhao et al, 2017 ). Interestingly, the further analysis found that the flukes parasitic in amphibians (frogs) formed one group, and the flukes from ruminants (cattle, sheep, ect) clustered together and formed another group.…”
Section: Resultssupporting
confidence: 92%
“…There were only one NCR in both D. japonicus and D. mehari , which were similar to D. nigromaculati (MW698822). However, this was different from other trematodes in superfamily Paramphistomoidea, such as F. cobboldi , O. streptocoelium , G. crumenifer , P. cervi , P. leydeni and F. elongatus , which had two NCRs ( Yan et al, 2013 ; Ma et al, 2015 ; Yang et al, 2016 ; Zhao et al, 2017 ; Han et al, 2020 ). In Paramphistomoidea trematodes, the longest overall NCR length was G. crumenifer (813 bp) and the shortest overall NCR length was O. streptocoelium (310 bp).…”
Section: Resultscontrasting
confidence: 58%
See 2 more Smart Citations
“…Rumen flukes infect ruminants and consist of a number of different species of the Paramphistomidae family (Gunathilaka et al, 2018). This family includes, for example, the genus Paramphistomum, Calicophoron, Cotylophoron, Ceylonocotyle, Gastrothylax, Fischoederius, Carmyerius, Gastrodiscus and Pseudodiscus (Torres-Acosta et al, 2012;Zhao et al, 2017;Kotze et al, 2020). Rumen fluke parasites impact hugely on livestock productivity by affecting growth rates, fertility, meat quality, wool or milk production, and they sometimes cause mortality.…”
Section: Introductionmentioning
confidence: 99%